Longitudinal fecal microbiota and volatile metabolomics preceding necrotizing enterocolitis in preterm infants: a case–control study - S. el Manouni el Hassani; N. M. Frerichs; D. J. C. Berkhout; T. Nijsen; H. H. Knobel; H. Weda; M. Xu; X. Long; L. Wijnoltz; M. M. van Weissenbruch; A. H. van Kaam; V. Cossey; et al. (Scientific Reports)
Abstract Alterations in fecal microbiota and volatile organic compound (VOC) profiles of preterm infants have been demonstrated before onset of necrotizing enterocolitis (NEC). However, NEC-specific signatures need to be identified before potential application as predictive biomarker in clinical practice. A prospective multicenter case–control study was conducted to identify preclinical fecal microbiota and VOC profiles of infants that developed NEC. Microbiota analysis (PCR-based IS-pro technique) and VOC analysis (gas chromatography-mass spectrometry) were performed on fecal samples collected up to three days before clinical NEC onset. In 112 infants (56 NEC, 56 matched controls), sufficient number fecal samples were collected for either microbiota or VOC analysis. Prior to NEC onset, Clostridium perfringens (p = 0.023, unadjusted) was more present in infants with NEC, versus controls. VOC analysis showed a clear distinction between fecal profiles of NEC cases and controls (area under the curve = 0.82). Fourteen unique VOC features contributed to this discrimination. Fecal microbiota and VOC profiles may serve as early indicators of NEC, and allow for increased understanding of pathophysiological mechanisms of NEC, but larger validation cohorts are needed before an overarching NEC-specific predictive microbiota-based biomarker can be implemented.